2015
DOI: 10.1007/s00300-015-1691-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation of phytoplankton in Admiralty Bay, South Shetlands: the dynamics of summer blooms shown by pigment and light microscopy analysis

Abstract: We conducted an integrated study of phytoplankton taxonomic composition, biomass and physicochemical properties of the water in Admiralty Bay, South Shetlands. The aim of the study was to provide detailed information on phytoplankton composition and diversity related to relevant environmental conditions. High-performance liquid chromatography pigment analysis and microscopy were performed in the summers of 2007 and 2009-2010. Results for 2007 showed a typical high-nutrient, low-chlorophyll system. Total carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
4
8
0
1
Order By: Relevance
“…Marguerite Bay (sector 10) experienced a significant decrease in total biomass over the past 15 years (Rozema et al, 2017), due to increases in temperature (Boyce et al, 2010;Schloss et al, 2014). The chlorophyll a data of the present study follow this trend for some regions of WAP (Table 3), with values around 0.5-2.0 mg.m −3 (Lange et al, 2007;Wasiłowska et al, 2015). Exceptions were in cases of blooms (e.g., Wasiłowska et al, 2015 sector 1;Schloss et al, 2014 sector 2;Lange et al, 2018 sector 2;Aracena et al, 2018 sector 3; Table 3).…”
Section: Discussion Environmental Patterns In Admiralty Bay In the Cosupporting
confidence: 74%
See 3 more Smart Citations
“…Marguerite Bay (sector 10) experienced a significant decrease in total biomass over the past 15 years (Rozema et al, 2017), due to increases in temperature (Boyce et al, 2010;Schloss et al, 2014). The chlorophyll a data of the present study follow this trend for some regions of WAP (Table 3), with values around 0.5-2.0 mg.m −3 (Lange et al, 2007;Wasiłowska et al, 2015). Exceptions were in cases of blooms (e.g., Wasiłowska et al, 2015 sector 1;Schloss et al, 2014 sector 2;Lange et al, 2018 sector 2;Aracena et al, 2018 sector 3; Table 3).…”
Section: Discussion Environmental Patterns In Admiralty Bay In the Cosupporting
confidence: 74%
“…It should be noted that although the phytoplankton community and events of Antarctic blooms are commonly dominated by diatoms, other taxa are also important components of the trophic web (Henley et al, 2019). Increases in cryptophytes and other flagellates have previously been reported (e.g., Phaeocystis antarctica and Gymnodiniales), as well as the substitution of diatoms for these flagellates in WAP, due to the influence of sea ice melt (Moline et al, 2004;Mendes et al, 2013;Lange et al, 2014;Mendes et al, 2017), as observed in the WAP sectors of the present study (Figure 3): sector 1 (Wasiłowska et al, 2015), sector 4 (Mendes et al, 2012(Mendes et al, , 2013, oceanic regions of sectors 5 (Mar de Weddell) and 6 (Passagem de Drake) (Mendes et al, 2012), as well as sectors 7 (Mendes et al, 2018), 9 (Gerlache Strait) (Mendes et al, 2017;Russo et al, 2018) and 11 (Arrigo et al, 2017).…”
Section: The Relationship Between Microphytoplankton Community Structsupporting
confidence: 68%
See 2 more Smart Citations
“…En particular, los estudios relacionados con la composición del fitoplancton en el sur de las Islas Shetland y los alrededores de la PA han sido relativamente abundantes (García-Muñoz et al 2013). Recientemente en la bahía Almirantazgo se ha reportado una dominancia de nanoflagelados en número y biomasa sobre diatomeas del microplancton, en las cercanías de la zona costera de la estación Polaca Henryk Arctowski, donde se encontró una tendencia de disminución de dichas diatomeas en la contribución total, de 44% entre 1996-1998 a 5% entre 2003-2005(Wasilowska et al 2015. Adicionalmente, Vanzan et al (2015) mostraron una alternancia estacional entre nanoplancton y picoplancton asociado al sistema de corrientes de mesoescala y el pastoreo estacional, donde sugieren que a futuro se debe desarrollar trabajos para comunidades < 20 µm para estudiar los efectos en la trama trófica microbiana y sus posibles efectos ambientales en altos niveles tróficos de las zonas costeras de la bahía Almirantazgo.…”
Section: Introductionunclassified